Defects and interface states related photocatalytic properties in reduced and subsequently nitridized Fe3O4/TiO2. Issue 6 (June 2018) - Liu, Chang; Zhu, Xiang; Wang, Peng; Zhao, Yisen; Ma, Yongqing
Abstract: The Fe3 O4 @TiO2 catalyst was reduced in a mixed H2 /N2 atmosphere at temperatures of 400, 600, 800 and 1000 °C in order to produce the oxygen vacancies (Ov ) and Ti 3+ ; Simultaneously, Fe3 O4 was reduced to Fe, a strongly magnetic material, beneficial for the magnetic separation after the photo-degradation. The optimal catalyst was obtained at the reducing temperature of 800 °C, which possesses the good photocatalytic performance and recycled activities; Moreover, its saturation magnetization M s is highest, reaching 23.8 emu g −1 which improves the magnetic separability. This optimal catalyst was subsequently treated in the NH3 atmosphere at temperatures of 500, 600 and 700 °C, aiming to investigate the effects of N-doping in TiO2 . The 600 °C treated catalyst exhibited the optimal photocatalytic performance. The factors that affect the photocatalytic performance are revealed and discussed in detail, including the ratio of Ov and N dopant in TiO2 as well as the interface states between TiO2 and the magnetic particles.